The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12053-015-9393-8
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking and tracking domestic gas and electricity consumption at the local authority level

Abstract: Government, local authority and industry initiatives to improve the energy efficiency of housing stocks are central to national and international commitments to reduce carbon dioxide emissions. To be effective, initiatives need to target homes which, given their location, size, fuel type and occupancy, use more energy than expected. This paper illustrates how energy efficiency benchmarks can be developed that account for these factors and highlights the shortcomings of relying on simple energy consumption stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…SIMD are reported as data zones which contain, on average, around 350 households (around 800 people), and correspond to administrative and political boundaries. The datazones are similar to the super output areas used in England, meaning the results of analyses using them are broadly comparable with English studies (such as Morris et al, 2016) 88 . However, as they are population-based, the datazones vary significantly in size, meaning that low density rural data zones covering multiple small population centres would be expected to be less homogenous than the small datazones in dense urban areas -a problem which is more significant in Scotland due to its more distinct urban-rural divide and the nature and distributions of rural and island populations.…”
Section: Measuring Fuel Povertysupporting
confidence: 76%
“…SIMD are reported as data zones which contain, on average, around 350 households (around 800 people), and correspond to administrative and political boundaries. The datazones are similar to the super output areas used in England, meaning the results of analyses using them are broadly comparable with English studies (such as Morris et al, 2016) 88 . However, as they are population-based, the datazones vary significantly in size, meaning that low density rural data zones covering multiple small population centres would be expected to be less homogenous than the small datazones in dense urban areas -a problem which is more significant in Scotland due to its more distinct urban-rural divide and the nature and distributions of rural and island populations.…”
Section: Measuring Fuel Povertysupporting
confidence: 76%
“…In the long run, the analysis of China's household carbon emissions can deepen our understanding of the diversity of the influencing factors. Through an analysis of the UK's situation, Brand et al found that employment status, car ownership, and commuting distance are the most important factors affecting household carbon emissions, followed by family income, property quantity, education level, and other factors [38] Morris et al point out the significant influence of climate, income, and the ratios of electricity to gas meters on household carbon emissions [39]. Although income has a positive impact on household carbon emissions, low-income, unemployed, and elderly groups may produce more carbon emissions, considering that the elderly group may feel colder and they are not constrained by carbon tax [40].…”
Section: Introductionmentioning
confidence: 99%
“…However, current UK policy is focused on directing a compulsory levy imposed on electricity suppliers towards those areas ranking highest for income deprivation, such as the Energy Company Obligation (ECO) and its predecessor, the Community Energy Saving Programme (CESP) (HM Government, 2009;Rosenow et al, 2013). Such schemes do not necessarily reach those most in need, due to the highly variable nature of household energy consumption which is strongly influenced by socio-economic factors (Morris et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the Green Deal was launched in 2011 to 'support the retrofit of 1.4 million homes' by 2020, focused on creating markets for energy efficiency measures and aimed at incentivising owners to invest in measures and receive pay-back from reduced energy bills (Rosenow et al, 2013;Hope and Booth, 2014;Morris et al, 2016). In principle, the Green Deal's payback mechanism, combined with the 2011 Energy Act which prevented landlords from refusing 'reasonable' requests from tenants for energy efficiency improvements should have helped overcome the split-incentive problem that persists in the private rented sector, where upgrading the energy efficiency of the dwelling is the responsibility of the landlord, yet tenants receive the benefit through lower energy bills and increased internal warmth (Ambrose, 2015;Leicester and Stoye, 2016).…”
Section: Introductionmentioning
confidence: 99%